VALUES FOUND IN LEWISâ€™S THE CHRONICLES OF NARNIA - Gusti Ayu Made Rai Suarniti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
Title of this paper is â€œValues Found in Lewisâ€™s The Chronicles of Narniaâ€. The objectives of this research are to find out the values found in The Chronicles of Narnia and to know how the moral values in The Chronicles of Narnia applied for moral education. The method steps consist of three, those are: reading the data source, the selection of the data from the data source, and the analysis of the data taken from the data source. The data for this research is taken from C.S. Lewisâ€™s The Chronicles of Narnia. The result of this research shows that there are a lot of values that appear on this novel, such as wisdom, generosity, patience, friendliness, prudence, honesty, justice, friendship, compassion, reasonableness, conscientiousness, self-discipline, industriousness, cooperativeness, self-reliance, courage, not selfish, courteousness, loyalty, thoughtfulness, sacrifice, dependability, trust, tolerance. This novel taught how to be a good human and taught how attitude in daily life. This novel is really good for moral education.